ANALISIS KEBERLANJUTAN USAHATANI HORTIKULTURA SAYURAN PADA LAHAN BERLERENG DI HULU DAS JENEBERANG, SULAWESI SELATAN - Saida, Saida; Sabiham, S; Widiatmaka, Widiatmaka; Sutjahjo, S H (LPPM Universitas Terbuka, 2011)
This study aimed to analyse the sustainability of vegetables horticultural farming on sloping land in the upstream Jeneberang watershed based on the index evaluation and the status of sustainability by Rap-farm method using Multidimensional Scaling (MDS).Results of ordination technique analysis Rap-farm method of MDS showed that index of vegetables horticultural farming sustainability ranged from 32.19-62.53. Dimension of ecological, economical, institutional, and technological included into sustainable enough category, while social dimension, included into less sustainable category in vegetables horticultural farming systems.Results of leverage Rap-farm analysis showed that from 43 attributes that were analyzed, there were 23 sensitive attributes that affected into the sustainability of vegetables horticultural farming systems in the upstream of Jeneberang watershed.